The Prevalence and Risk Factors of Constipation in Pregnancy - Hestiantoro, Andon; Baidah, Priska A (Indonesian Socety of Obstetrics and Gynecology, 2018)
Objective: To estimate the prevalence of constipation inpregnancy and correlation between gestational age, dietaryfiber intake, water comsumption, and physical activity.   Methods: This study used cross-sectional design with samples of174 healthy pregnant women undergoing antenatal care atObstetrics and Gynecology Outpatient Clinic RSCM during August -October 2016. Data were collected using questionnaire. Diagnosisof constipation was based on ROME III criteria, dietary fiber ismeasured using Food Frequency Questionnaire (FFQ), and physicalactivity was measured using International Physical Activity Questionnaire(IPAQ). Chi-square and Fisher’s exact test were conducted toevaluate the association between variables.   Results: The prevalence of constipation in pregnant womenobserved in this study was 13.2% (95% CI 8.3-18.1). The mostfrequent complaints included straining, incomplete evacuation,and anorectal obstruction. Dietary fiber intake was low in 81.03%subject. with average dietary fiber intake of 18.97 gram/day.There was no significant association between constipation andgestational age (OR 4.36, 95%CI 0.51-37.48 for second trimesterand OR 2.04, 95%CI 0.25-16.7 for third trimester), dietaryfiber intake (OR 0.82, 95%CI 0.28-2.39), water consumption(OR 1.38, 95%CI 0.56-3.41), and physical activity (OR 1.167,95%CI 0.28-4.87).   Conclusion: Prevalence of constipation in pregnant women is13.2%. There is no significant correlation between gestational age,dietary fiber intake, water consumption, and physical activity.   Keywords: constipation, pregnant woman, ROME III